2007
DOI: 10.1016/j.febslet.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of trophinin in human endometrial surface epithelia by CGβ and IL‐1β

Abstract: During embryo implantation, trophinin mediates cell adhesion by homophilic binding at the apical surfaces of trophectoderm and endometrium. Trophinin is expressed on the human endometrial epithelia in rare occasions. We developed hCGcoated agarose beads that mimic the physical and physiological features of an implantation-stage human blastocyst. When hCG-coated beads were applied to human endometrial epithelial cells in the presence of IL-1b, endometrial cells acquired strong trophinin expression and the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…5 Trophininexpressing primary cultured endometrial cells exhibited apical adhesion to HT-H cells. 5 When GWRQ was added to trophininexpressing primary cultured human endometrial epithelial cells, we observed apoptosis (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Trophininexpressing primary cultured endometrial cells exhibited apical adhesion to HT-H cells. 5 When GWRQ was added to trophininexpressing primary cultured human endometrial epithelial cells, we observed apoptosis (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5]7,9 In the first trimester placenta, invasive extravillous cytotrophoblasts confront the endometrial glandular epithelia, initiating the steps required for blood vessel formation of the placenta. 22 Trophinin expression by extravillous cytotrophoblasts (Sup.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 2 more Smart Citations
“…At the first steps of implantation, hCG is able to prolong the WOI, by inhibiting decidual Insulin like Growth Factor (IGF)-Binding Protein and IGFI (both markers of complete decidualization) (Fluhr et al, 2008b), and in association with interleukin 1 (IL-1), to favor adhesion via the increase in trophinin expression on endometrial epithelium (Sugihara et al, 2008). Concerning trophoblast functions hCG (and its hyperglycosylated variant) has been demonstrated to promote trophoblastic cells migration, and to reduce endometrial barrier, through its action on matrix metalloprotease protein 9 (MMP9, increased), TIMP-1, -2, -3 (reduced), GM-CSF, IL-11 Fluhr et al, 2008a;Paiva et al, 2011).…”
Section: Embryonic Signals: Example Of the Embryo-specific Hcgmentioning
confidence: 99%